Análisis de los servicios turísticos gastronómicos que se ofrecen en la ciudad de Babahoyo - Freire Gamboa, Melissa Xiomy (2020)
The current case study is aimed at the Gastronomic Tourist Service and the offer in the city of Babahoyo, and to know the socio-economic and cultural identity impact generated by the relationship between both factors that contributes to the location and the region; It should be noted that gastronomy is one of the key tools for the improvement of tourism in Babahoyo. This research aims to encourage and preserve the intrinsic traditions in the Ancestral Identity of Montubio Fluminense’s, representing the varieties of typical dishes that are native to the city, where you can know the level of acceptance of the Gastronomic Tourist Services in the population. The feasibility and significance of the project will be achieved; and analyze the behavior of the tourism market that provides minimal information about this Gastronomic Tourism Sector.